Homoeopathic Management of Acute Behavioral Disturbance of Athletes: A Case Report (Advancements in Homeopathic Research, 2022)
The athletes are most vulnerable to suffer from any mental disorders. The competitive nature of this genre leads to lot of societal pressures and self-esteem issues. Data suggests that there is a broadly high prevalence of mental disorders in elite athletes as compared to the general population.1 The acute behavior disturbance due to performance failure is an emergency area, often visible among elite athletes and demands a careful management. A case of such critical situation was treated with Homoeopathy, following Dr. Hahnemann’s treatment guidance on acute mental disease management, without any Psychotherapy. The significant improvement was observed within reasonable time without any recurrence reported even after one year. Belladonna was found useful for acute behavioral disturbance management.
Keywords: Athletes; Acute behavioural disturbance (ABD); Belladonna; Homeopathy, Sports Psychiatry